3-({4-[(2-Methylbenzylidene)amino]-5-sulfanylidene-1H-1,2,4-triazol-3-yl}methyl)-1,3-benzoxazol-2(3H)-one - Aydn A.; Hekimoğlu N.; Akkurt M.; Önkol T.; Çiçekli S.U.; Büyükgüngör, Orhan (International Union of Crystallography (IUCr), 2013)
In the title compound, C18H15N5O2S, a weak intramolecular C—H...S hydrogen bond results in a small dihedral angle of 3.71 (9)° between the methylphenyl and triazole rings, which, in turn, form dihedral angles of 80.09 (8) and 77.32 (8)°, respectively, with the benzoxazolone mean plane. In the crystal, N—H...O hydrogen bonds link molecules into chains along [001], and weak C—H...N hydrogen bonds and π–π interactions between the five- and six-membered rings [centroid–centroid distances = 3.5074 (11) and 3.616 (1) Å] consolidate the crystal packing.
Keywords: mean ?(C-C) = 0.003 Å; data-to-parameter ratio = 16.7; wR factor = 0.110; T = 296 K; Crystallography; QD901-999; single-crystal X-ray study; Organic Papers; R factor = 0.042